Organic matter mineralization in modern and ancient ferruginous sediments - André Friese (Nature Portfolio, 2021)
The conditions that shaped Earth’s evolution during the Archaean and Proterozoic Eons remain unknown. Using Lake Towuti in Indonesia as an analog of early oceans the authors find that microbial methanogenesis exerts a strong influence with important implications for the composition of Earth’s early atmosphere.